Vínculos transitórios: psicoterapia on line na sociedade pandêmica - Vasques, Juliana Pereira Damasceno (Universidade Federal de São Carlos, 2023)
The new coronavirus pandemic has transformed habits across society around the world. As a result, technologies played a fundamental role in the most sensitive changes, re-signifying customs and professional routines, in social and consumer relations - and even in apparently immutable conventions. This exploratory project deals with the increase in online psychological and psychotherapeutic follow-up services and their immense demand in this unprecedented condition. A year and a few months after the declaration of the pandemic by the World Health Organization (WHO), however, the practice not only seems far from being ended, but can still be improved, with the emergence of a series of electronic service platforms, each more and more possible resources for the establishment of the so-called home-office and a delicate search - and increasingly critical - of subjects in the process of psychic illness, in addition to solutions as fast as the bytes and megs exchanged in minutes of consultation. How, therefore, is the question of the concept of work aligned with the production of meanings and subjectivities of the subjects, in this new format? Through the "snowball" method, which uses reference chains, we propose a qualitative, exploratory study with psychology workers, and a more in-depth analysis of this historical period, in a cut and a look more aimed at professionals, their needs and anxieties, faced with unprecedented personal and professional dilemmas.
Transient bonds: online psychotherapy in pandemic society
Liens transitoires : psychothérapie en ligne dans une société pandémique
Keywords: comunicação digital; psicoterapia online; setting; covid-19; saúde mental; psychoterapy online; digital communication; setting; mental health; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA